2000
DOI: 10.1037/0021-9010.85.6.940
|View full text |Cite
|
Sign up to set email alerts
|

Validity of measures of cognitive processes and general ability for learning and performance on highly complex computerized tutors: Is the g factor of intelligence even more general?

Abstract: Theoretical arguments and analyses from 2 studies provide compelling evidence that computerized measures of information-processing skills and abilities are highly useful supplements to more traditional, paper-based measures of general mental ability for predicting individuals' capacity to learn from and perform on highly challenging, multifaceted tutors. These tutors were designed to emulate learning and performance in complex, real-world settings. Hierarchical confirmatory factor analysis provided evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
0
11
0
1
Order By: Relevance
“…So, equivalence research per definition does not take the opportunity to improve the quality of assessment. Roznowski et al (2000) offered an illustration of the use of cognitive processing measures that explicitly build on the possibilities of computerization to go beyond the type of measurement possible with paper-and-pencil testing and show incremental validity over a general cognitive measure in predicting training performance.…”
Section: Improved Administrative Ease With Which Selection Systems Camentioning
confidence: 99%
“…So, equivalence research per definition does not take the opportunity to improve the quality of assessment. Roznowski et al (2000) offered an illustration of the use of cognitive processing measures that explicitly build on the possibilities of computerization to go beyond the type of measurement possible with paper-and-pencil testing and show incremental validity over a general cognitive measure in predicting training performance.…”
Section: Improved Administrative Ease With Which Selection Systems Camentioning
confidence: 99%
“…For example, Ree and Carretta (1994) factor analyzed the Armed Services Vocational Aptitude Battery (ASVAB) in a large sample of US high-school and college-age individuals, essentially replicating Vernon's (1950) hierarchical structure, with g as the general factor and Cognitive Speed, Verbal/Numerical and Technical Skills factors beneath. When more diverse batteries are factor analyzed, for example, batteries that contain additional measures of cognitive processes, somewhat different hierarchical structures emerge, although a general ability factor is at the apex (e.g., Roznowski, Dickter, Hong, Sawin and Shute 2000). We summarize the existing literature on group-mean differences at the level of g and at levels that are narrower theoretically but are practically useful (and used in practice) in employment testing.…”
Section: Cognitive Abilitiesmentioning
confidence: 99%
“…educational attainment) and on career choices (Melamed, 1996a). Furthermore, general mental ability relates to job performance (Ree, Earles, & Teachout, 1994;Roznowski, Dickter, Hong, Sawin, & Shute, 2000); and performance in the various jobs undertaken in the course of the career must also influence extrinsic career success. Indeed, Judge et al (1999) identified a positive relationship between general mental ability and extrinsic career success.…”
Section: Hypothesesmentioning
confidence: 99%